First Year Survey of Arthropods in California Hemp - Britt, Kadie E.; Meierotto, Sarah; Morelos, Victoria; Wilson, Houston (Frontiers in Agronomy, 2022)
Hemp is a newly (re)introduced crop to United States and California agriculture. A study was initiated in the summer of 2021 to survey the arthropods present in hemp in two regions of California: Fresno County in the Central Valley and Ventura County along the Central Coast. Eight hemp plots were sampled every two weeks from August to mid-October using a combination of D-vac samples, leaf collections, and visual observations. All samples were processed and ultimately recorded as the total number of specimens collected per morphospecies across all sampling dates, further broken down to express the number of specimens collected from the Central Valley and the Central Coast. D-vac sampling was the most reliable method for specimen collection and led to the recovery of arthropods from 11 orders, 69 families, and 157 morphospecies. Approximately 13,000 specimens were collected and processed, half of which were whiteflies (Hemiptera: Aleyrodidae). Of the specimens recovered, Hemiptera was the most representative order (with and without whiteflies), followed by Thysanoptera and then Hymenoptera. The most frequently collected specimen was Engytatus modestus (Hemiptera: Miridae). Very few pest species were recovered, cannabis aphid (Phorodon cannabis) being the only one that was observed in any noticeable density. Many generalist predators and parasitoid wasps were also collected. Findings from this survey provide baseline information on the arthropod species present in California hemp. This survey will be repeated and expanded in future growing seasons.